Business Planning for Muslim Fashion Enterprise - Rahmat, Muhamad Radhitya; Yulianti, Ida (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to develop a systematic and comprehensive business plan for Griya Yasmine to strengthen its competitiveness and support sustainable business growth amid the dynamic challenges faced by MSMEs. Design/Methodology/Approach – This study adopts a business planning approach by formulating detailed functional strategies across key business areas. The planning process encompasses marketing, operations, organizational structure, and financial planning to develop an integrated and feasible business plan that supports long-term business development. Findings – The study produces a comprehensive business plan for Griya Yasmine. The proposed plan includes a marketing strategy targeting Muslim women consumers through integrated online and offline channels, a more efficient operational workflow, a well-defined organizational structure to facilitate business expansion, and projected financial statements to support strategic planning and managerial decision-making. These strategies provide a practical roadmap for achieving sustainable business growth. Originality/Value The study offers value by presenting a comprehensive, function-based business plan specifically designed for a Muslim women–focused MSME, providing a practical model that can be adapted by similar businesses to improve long-term strategic direction.